Territorial transformations in agriculture of Chernihiv region in the context of climate change: the case of corn and sunflower - Baranovskyi, Mykola; Hlushko, Denys (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Introduction. Different crops and regions of Ukraine are characterized by unequal dependencies on climate change. This situation creates a demand for scientific research to analyse «climate-agricultural production» dependence at the regional level. Chernihiv region, whose territory is located in two environmental zones, is an ideal testing ground for assessing territorial transformations in agricultural production under the influence of climate change. The purpose of article. The purpose of the study was to identify territorial transformations in agricultural production of Chernihiv region that were formed under the influence of climate change during 2001-2020, using corn and sunflower as an example. Additionally, the impact of climate factors on the yield of the selected crops in the region was assessed. Research methods. The study was based on data on gross harvest and yields of the selected crops, corn and sunflower, in Chernihiv region during 2001-2020. Climate trends were represented by average air temperature and precipitation during the growing season for the same period. Spatial transformations of the region’s agricultural production were determined using the territorial concentration index. A number of calculations were carried out to assess the contribution of climatic factors to the dynamics of yields of the selected crops. They included the determination of 1) trend yields; 2) total and agrotechnical variance; 3) the share of the climatic factor in the total variance. Main findings. In 2001-2020, Chernihiv region observed a significant increase in heat supply, the length of the growing season, and the sum of effective temperatures. The climate trends of this period created suitable conditions for expanding of a number of heat-tolerant crops, including corn and sunflower, into the region. The study used them as selected crops to assess territorial transformations in agricultural production of this northern region of Ukraine. The analysis of statistical data showed that the sown area and gross harvest of corn and sunflower increased tenfold in Chernihiv region, and the local agroclimatic zones of their cultivation moved 125-150 km north. The main producers of corn and sunflower are still the forest-steppe areas of the region. At the same time, its Polissya part currently produces 25 to 30% of the gross harvest of these crops. Due to climate change in the region, the yield of the selected crops has increased significantly, exceeding the national average values by 37-43%. The «migration» of heat-tolerant crops to the region has considerably changed the specialization of agricultural production in this Polissya region. Based on the calculations, it was found that the contribution of the climatic factor to corn yields was maximum in 2001-2010 - 74%. The contribution of climatic trends to sunflower yield of the region was significantly lower - 53-56 % in different periods. Taking into account the results obtained, the study points out the need to develop effective measures for adapting agricultural production in Chernihiv region to climate change. Scientific novelty and practical value. The article describes for the first time the characteristics of territorial transformations in agricultural production of Chernihiv region in the context of climate change and assesses the contribution of the climatic factor to the dynamics of productivity of the selected crops in the region. The practical value of the study is the possibility of using its algorithm to conduct similar studies in other regions of Ukraine. The results of the study are important in the context of substantiating regional measures to adapt agricultural production to climate change.